Allocentric directional processing in the rodent and human retrosplenial cortex - Knight, Rebecca; Hayman, Robin (Frontiers in Human Neuroscience, 2014)
Head direction cells in the rodent brain have been investigated for a number of years, providing us with a detailed understanding of how the rodent brain codes for allocentric direction. Allocentric direction refers to the orientation of the external environment, independent of one's current (egocentric) orientation. The presence of neural activity related to allocentric directional coding in humans has also been noted but only recently directly tested. Given the current status of both fields, it seems beneficial to draw parallels between this rodent and human research. We therefore discuss how findings from the human retrosplenial cortex, including its ‘translational function’ (converting egocentric to allocentric information) and ability to code for permanent objects, compare to findings from the rodent retrosplenial cortex. We conclude by suggesting critical future experiments that derive from a cross-species approach to understanding the function of the human retrosplenial cortex